2013
DOI: 10.1111/aji.12112
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Levels of Folate Receptor‐β and Reduced Numbers of Fetal Macrophages (Hofbauer Cells) in Placentas from Pregnancies with Severe Pre‐Eclampsia

Abstract: Problem Preeclampsia (PE), a pregnancy complication of unknown etiology, is a major cause of maternal and fetal mortality and morbidity. Previous studies have described placental genes which are up-regulated in expression in PE, but few studies have addressed placental gene suppression in this syndrome. Method of Study Gene profiling and quantitative reverse transcription PCR (qRTPCR) analyses were used to identify genes down-regulated in placentas from women with severe preterm PE compared to gestational ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 72 publications
4
55
0
Order By: Relevance
“…FGR was defined as weight < 10th percentile for gestational age at birth in pregnancies not complicated by preeclampsia. A detailed description of these patients was previously reported [3941]. …”
Section: Methodsmentioning
confidence: 99%
“…FGR was defined as weight < 10th percentile for gestational age at birth in pregnancies not complicated by preeclampsia. A detailed description of these patients was previously reported [3941]. …”
Section: Methodsmentioning
confidence: 99%
“…29 Conversely, we documented reduced HBC numbers in pregnancies with preeclampsia (PE). 30 Adverse neonatal outcomes including cerebral palsy are associated with preterm birth and HCA when accompanied by fetal inflammatory response syndrome (FIRS, a multisystemic microbial invasion of the fetus with the hallmark presentation of funisitis). [31][32][33] In situ RT-PCR revealed an infectious agent was present in 46 of the 60 placentas from newborns with respiratory distress and severe neurological sequelae.…”
Section: The Role Of Hofbauer Cells and Evidence For Their Microbiamentioning
confidence: 99%
“…Abnormal quantity of M1/M2 macrophages may result in PE . It is reported that PE is associated with a change in phenotype and function toward the M1/proinflammatory macrophage continuum . However, the reason why macrophages polarization changed in PE is unknown.…”
mentioning
confidence: 99%